Humphrey's really wheely racing day - Birney, Betty G. (Birney, Betty G. Humphrey's tiny tales, 2014)
"When Mandy, one of the students from classroom 26, brings a special hamster-sized racecar to class, it means just one thing--Humphrey is going to be in a hamster race"--